An Analysis of Classroom Interaction Using Flint System in Online Learning During Pandemic Covid-19 : Indonesia - Dice Lestari, Dice Lestari; Ali Akbarjono; Feny Martina (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
Classroom interaction is not only carried out during face-to-face learning, but also in online learning. As we know that classroom interaction an important component to achieve the effectiveness in the learning process. This study aims to find out how is the classroom interaction between English teacher and students in online learning during pandemic Covid-19. This type of research was descriptive qualitative, so the researcher used observation, interview and documentation for collection the information and data. The students of MAN 2 Kota Bengkulu at XI IPS 1 as the subject of this research, the researcher needs a systematic procedures in analyzing the data in order that the result can be organized systematically. The result showed that the classroom interaction between English teacher and the students was good. The most frequently utterances did by the teacher was ask question, give information and correct direction. Whereas, student response, specific and student response open-ended or student initiate mostly for the students talk categories.